Politics and governance in Indian states Bihar, West Bengal and Tripura - Mitra, Subrata Kumar 1949-; Bhattacharyya, Harihar 1959- (World Scientific, 2018)
"Understanding India's politics and governance requires an examination of how politics and governance occur in the regional States, which constitute the federal units of India. This book addresses the issues of federalism, power-sharing and constitutional reforms, and their effects on governance in Indian States. Located within the growing literature on new State politics in India, this volume presents a critical, in-depth analysis of politics in Bihar, West Bengal and Tripura ... these States being units of analysis for more general implications. What common obstacles have impeded development in each State, and what factors have favored recent, rapid development in some States but not others? The issues of caste conflicts, ethnic conflicts and other collective identity issues will be examined in this book ... a pioneer volume with detailed, empirically-based research on the implications of State-centric politics in India"...